PERANCANGAN SISTEM INFORMASI PENERIMAAN PESERTA DIDIK BARU (PPDB) BERBASIS WEB PADA MA ARGAYASA JALATRANG DENGAN MENGGUNAKAN METODE AGILE - Abdurahman, Dani; Sidiq, Maulana; Dwicahya Supriatman, Rian (Jurnal Mahasiswa Sistem Informasi Galuh, 2025)
MA Argayasa Jalatrang is an educational institution that focuses on developing students' morals and personalities. Every year, around 30 prospective students register, and the registration process, which is still carried out conventionally, takes about a week. This process involves taking forms at the counter and recording data manually, which often causes data redundancy and delays in reporting. To overcome this problem, a computerized system is needed so that registration can be done more easily, quickly, and efficiently. The agile method is used in the development of a web- based new student registration information system application. The results of the study show that this application helps staff in creating reports faster and reduces data redundancy, so that the management of applicant data becomes faster, more accurate, and more efficient.